Karakteristik Morfologi dan Analisis Kandungan Senyawa Fitokimia Berbagai Tapak Dara (Catharanthus roseus) - Malpida Ulpa; Kamsia Dorliana Sitanggang; Hilwa Walida; Yusmaidar Sepriani (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2022)
Palm flower is a plant that is widely distributed in the tropics. Originally from Madagascar, it was known as Madagascar periwinkle. The components of active compounds present in blood sites are phenolic acids, alkaloids, and flavonoids. Palm flower leaves contain a lot of flavonoid compounds that function as antioxidants, stimulate the production of nitrite oxidants (can dilate blood vessels), inhibit erythrocyte clumping, and can inhibit the growth of cancer cells. This study aims to observe the morphological characteristics and determine the content of phytochemical compounds in various varieties of palm flower (Catharanthus roseus) collection of the Labuhanbatu University experimental garden. The materials used in this study were 4 types of palm flower plant varieties collected by Labuhanbatu University. The method in this research is a survey with a qualitative approach to collect information related to the collected data. The results of observations of morphological characteristics were differences in stem color and flower color of palm flower and differences in flavonoids in each palm flower, and palm flower TW was palm flower which had the highest flavonoid content, namely 663.80. Keywords: Palm flower, morphology, flavonoids